Review of the genus Taiwanomyrme Tsuneki, 1993 (Hymenoptera, Mutillidae, Mutillinae), with description of two new species from China - Tu, Bin-Bin; Lelej, Arkady S.; Chen, Xue-Xin (Zootaxa, 2015)
Five species of Taiwanomyrme Tsuneki, 1993 are reviewed; two of them, T. latisquamula Tu, Lelej et Chen, sp. nov. (China: Guizhou) and T. impressoides Tu, Lelej et Chen, sp. nov. (China: Zhejiang, Fujian, Hunan), are described and illustrated. Smicromyrme taiwanus Tsuneki, 1993 is proposed as a new synonym for Taiwanomyrme friekae (Zavattari, 1913). A key to males and females of Taiwanomyrme and additions to the key of females of Oriental genera of the tribes Petersenidiini and Trogaspidiini are given. New ranges are given for T. basirufus (Chen, 1957) and T. impressus (Chen, 1957), specifically within China.